The ecdysone receptor (EcR) is a major regulator of tissue development and growth in the marine salmonid ectoparasite, Lepeophtheirus salmonis (Copepoda, Caligidae) - Sandlund, Liv; Nilsen, Frank; Male, Rune; Dalvin, Sussie (Molecular and Biochemical Parasitology, 2016)
The function of the ecdysone receptor (EcR) during development and molting has been thoroughly investigated in some arthropods such as insects but rarely in crustacean copepods such as the salmon louse Lepeophtheirus salmonis (L. salmonis) (Copepoda, Caligidae). The salmon louse is an ectoparasite on Atlantic salmon that has major economical impact in aquaculture due to the cost of medical treatment methods to remove lice from the fish. Handling of salmon louse infestations is further complicated by development of resistance towards available medicines. Understanding of basic molecular biological processes in the salmon louse is essential to enable development of new tools to control the parasite. In this study, we found L. salmonis EcR (LsEcR) transcript to be present in the neuronal somata of the brain, nuclei of muscle fibres and the immature intestine of the salmon louse. Furthermore, we explored the function of LsEcR during development using RNA interference mediated knock-down and through infection trials. Our results show that knock-down of LsEcR in the salmon louse is associated with hypotrophy of several tissues, delayed development and mortality. In addition, combined knock-down of LsEcR/LsRXR resulted in molting arrest during early larval stages. publishedVersion